The Bidayuh Krokong Dialect: To Standardize or not Standardize - Jecky, Misieng (Macrothink Institute, USA., 2017)
The intricacies of language require all language scientists to be thorough and methodical in doing their analyses. This need is even more critical for the Bidayuh languages when there is a lot of on-going effort to preserve the language by various groups both from 21the people as well those from outside. Standardization and the teaching of the language in schools are among the top suggestions being explored. One of the disadvantages of standardizing a language is the danger of making the many different varieties to die out among the speakers. A closer look at one Jagoi sub-dialect commonly referred to as the Krokong dialect in comparison to other sub-dialects and dialects from other clusters illustrate some of the differences in pronunciation that can be found which highlights the need to help preserve if not all but most of the major varieties.